Dielectric and thermal properties of Na2O-CaO-SiO2-MgO-Al2O3-TiO2 glass-ceramic - Kaygili, Omer; Yakuphanoğlu, Fahrettin; Tatar, Cengiz (Korean Assoc Crystal Growth, Inc, 2016)
The Na2O-CaO-SiO2-MgO-Al2O3-TiO2 (NCSMAT) glass-ceramic having the composition of 49 Na2O, 19 CaO, 31 SiO2, 0.25 MgO, 0.50 Al2O3 and 0.25 TiO2 (wt.%) was prepared by conventional method. The crystal structure, phase composition, microstructural, chemical, thermal and dielectric properties of the glass-ceramic were investigated. Using the X-ray diffraction (XRD) results, biphasic structure of the glass-ceramic sample was detected, the crystallite size was found to be 13.21 nm for Na4CaSi3O9 phase and 11.02 nm for Na8Al4Si4O18 phase, and the crystallinity percent was calculated to be 86.74%. Scanning electron microscope (SEM) observations show that the NCSMAT glass-ceramic has the fine-grained particle distribution with the smaller particles than 1 mu m. The stretching modes of Si-O-Si bound were detected from Fourier transform infrared (FTIR) spectrum. The NCSMAT glass-ceramic is thermally stable from room temperature to 1173 K and the mass loss of the sample in this range is 1.05%. The density was calculated to be 2,751 kg m(-3). The relative permittivity at 1 kHz was found to be 85.35. The alternating current conductivity increases with increasing frequency and obeys the universal power law.
Keywords: Glass-ceramic; Crystal structure; Thermal stability; Dielectric properties